Occupational Stress and Job Satisfaction among Nurses Working in a Tertiary Care Hospital - Lamichhane, Rama Kumari; Dhakal, Bijaya; Thapa, Asha; Parajuli, Sumitra (International Journal of Silkroad Institute of Research and Training, 2024)
Background: Occupational stress and job dissatisfaction are prevalent issues among nurses employed in hospital settings.Occupational stress manifests as both emotional and physical reactions stemming from a perceived imbalance between anindividual's priorities and responsibilities. Conversely, job satisfaction is a critical determinant of the efficiency and productivityof human resources. This study aims to assess level of occupational stress and level of job satisfaction among nurses workingin tertiary care hospitals and to find out correlation between occupational stress and job satisfaction among nurses.Method: Descriptive study design was used; study sample was 226 nurses selected by enumerative sampling technique.The data was collected using self-administered questionnaire consisted of socio-demographic information, ModifiedExpanded Nursing Stress Scale and Job Satisfaction Scale. The collected data was entered into SPSS version 26 and wereanalyzed using descriptive and inferential statistics.Result: More than half (58.45%) of the respondents reported a moderate level of stress. Similarly, more than half (52.7%)of the respondents expressed satisfaction with their job. The study identified significant associations between age, maritalstatus, and number of children with the level of occupational stress among the respondents. However, no significantcorrelation was found between occupational stress and job satisfaction.Conclusion: Based on the findings, it can be concluded that a majority of the respondents are experiencing stress, whilemore than half of the nurses are satisfied with their job. The most satisfying factors identified include the nature of the workitself and the hospital environment in which they work.